2005
DOI: 10.2139/ssrn.870239
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Market Structure and Irreversibility on Investment under Uncertainty: An Empirical Analysis

Abstract: The empirical literature of investment under uncertainty has vastly neglected to account for the role played by market structure. Recently the theory has however started to merge real options theory with game theory to offer alternative explanations to strategic investment behaviour. This paper estimates an error correction model of investment under product price uncertainty for 23 French industries during the period 1977-1997 and represents the first empirical work that includes variables of market structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…By using industry level data from a panel of French two digit manufacturing industries and Herfindhal index as a proxy for competition, Maioli (2005) obtained similar results to Ghosal and Loungani (1996). She found that uncertainty has a negative and highly significant effect on investment.…”
mentioning
confidence: 67%
See 4 more Smart Citations
“…By using industry level data from a panel of French two digit manufacturing industries and Herfindhal index as a proxy for competition, Maioli (2005) obtained similar results to Ghosal and Loungani (1996). She found that uncertainty has a negative and highly significant effect on investment.…”
mentioning
confidence: 67%
“…According to the Model 2, DUMCR4 is statistically significant and has a negative effect on investment. The reductive effect of uncertainty on investment increases 6 Maioli (2005) also defined an industry as concentrated if the average value of the HHI was lying at or above the 75th percentile or the top 25th percentile (Maioli, 2005: 27 , "The Effects of Market Structure on Uncertainty-Investment Relationship: Evidence from Turkish Manufacturing Industry", Sosyoekonomi, Vol. 26(37), 185-200.…”
Section: Estimation Resultsmentioning
confidence: 99%
See 3 more Smart Citations